2015
DOI: 10.1152/japplphysiol.00299.2015
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical BACE1 content with one bout of exercise is accompanied by declines in AMPK, Akt, and MAPK signaling in obese, glucose-intolerant mice

Abstract: Obesity and type 2 diabetes are significant risk factors in the development of neurodegenerative diseases, such as Alzheimer's disease. A variety of cellular mechanisms, such as altered Akt and AMPK and increased inflammatory signaling, contribute to neurodegeneration. Exercise training can improve markers of neurodegeneration, but the underlying mechanisms remain unknown. The purpose of this study was to determine the effects of a single bout of exercise on markers of neurodegeneration and inflammation in bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 64 publications
4
60
0
Order By: Relevance
“…One study investigated the role of the PI3K/Akt pathway in APP processing suggesting that PI3K/Akt activation is associated with BACE1 expression in the brains of HFD-fed mice 55 . This finding is consistent with our data showing that the PI3K/Akt pathway is a key regulator of APP and BACE1 expressions in SK-N-MC cells treated with PA-BSA.…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the role of the PI3K/Akt pathway in APP processing suggesting that PI3K/Akt activation is associated with BACE1 expression in the brains of HFD-fed mice 55 . This finding is consistent with our data showing that the PI3K/Akt pathway is a key regulator of APP and BACE1 expressions in SK-N-MC cells treated with PA-BSA.…”
Section: Discussionmentioning
confidence: 99%
“…liver and triceps, respectively). Samples were then centrifuged at 1500 g (4°C) for 5 minutes (hypothalamus was centrifuged at 10,000 g for 15 minutes (MacPherson et al, 2015)), the supernatant was collected and a bicinchoninic acid (BCA) assay was performed to determine protein concentration (Smith et al, 1985). Separation of equal amounts of protein was completed using 10% SDS-PAGE gels followed by a wet transfer onto nitrocellulose membrane (100V for 60 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…), while a recent study examined diet‐induced obesity and glucose intolerance in mice, demonstrated an increase in ERK phosphorylation and a trend for increased p38 phosphorylation (Macpherson et al. ). A 1 year high‐sugar high‐fat diet resulted in increases in beta‐amyloid content along with increased phosphorylated JNK in the hippocampus of rats as early as 6 months (Niu et al.…”
Section: Introductionmentioning
confidence: 97%
“…Work from our group has demonstrated that high‐fat feeding of wild‐type C57BL6/J mice results in an increase in BACE1 activity (Macpherson et al. ). Furthermore, several rodent models of diabetes (genetic, diet and streptozotocin induced) results in increased BACE1 content and beta‐amyloid generation in the brain (Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation